Hip-hop autochtone au Québec. Oralités contemporaines au gré des ondes politiques et médiatiques - Audet, Véronique (Inter : art actuel, 2009)
An article from Inter, on Érudit.

Les voix du tambour. Traditions et innovations musicales chez de jeunes Atikamekw Nehirowisiwok, Québec - Jérôme, Laurent (Jeunesses autochtones. Affirmation, innovation et résistance dans les mondes contemporains, 2009)

Tusarnituuq! Nagano In The Land Of The Inuit - Lajeunesse, Félix (Filmoption International, 2009)
In September 2008 Canada’s most prestigious orchestra, the acclaimed Orchestre symphonique de Montreal (OSM), embarked on its first ever tour of the Canadian Arctic. Lead by internationally celebrated conductor Kent Nagano, the OSM's program featured a concert of music from the classical repertoire, including Stravinksy’s Histoire du soldat narrated in Inuktitut, the language of the Inuit people, and a new work inspired by Inuit throatsinging from Canadian composer Alexina Louie. Offering viewers intimate access to Maestro Nagano, the artists, and the remote Inuit communities they visit, this stunning documentary captures an extraordinary meeting of two worlds through music.

Du teueikan au hip-hop, des harangues à l’art action - Sioui Durand, Guy (Inter : art actuel, 2009)

"Eskimo chicks and word warriors": the creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

Identifications, relations et circulation des savoirs chez les Atikmakekw de la Haute-Mauricie. Un regard ethnographique sur le tewehigan - Jérôme, Laurent (La nature des esprits dans les cosmologies autochtones, 2007)

Essential Song: Three Decades of Northern Cree Music - Whidden, Lynn (Wilfrid Laurier University Press, 2007)
A pack that contains a book and a CD. The book presents an outline of Cree musical history and a contribution to ethnomusicology, social history, and Aboriginal studies. The CD contains over 80 Cree hunting songs.

Marc-Antoine Charpentier chez les Abénaquis ou la petite histoire d’une Chanson des Bergers au Nouveau-Monde - Dubois, Paul-André (Études d'histoire religieuse, 2006)

Alanis Obomsawin: The Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television. In this book, the first devoted to any Native filmmaker, Obomsawin receives her due as the central figure in the development of indigenous media in North America.

Innu Nikamu : expression musicale populaire, affirmation identitaire et guérison sociale en milieu innu contemporain - Audet, Véronique (Université Laval, 2005)

Les chansons et musiques populaires innues : contexte, signification et pouvoir dans les expériences sociales de jeunes Innus - Audet, Véronique (Recherches amérindiennes au Québec, 2005)
This article presents popular Innu musical expressions as voices that serve to reaffirm Innu identity and revitalize Innu society and culture. These songs in the Innu language are inspired by various musical trends such as country, rock, folk and pop, as well as Innu, Pan-Indian, Christian and Quebecois traditions. They have been created, practiced and renewed since the second half of the twentieth century, accompanying the often radical events, movements and transformations that have marked Innu social and cultural life. Contemporary Innu youth, like their predecessors, are the primary conveyers of this expressive movement which they use to participate in the daily life of their communities, and reaffirm their identity, their experiences and their preoccupations, thus contributing to the revitalization of their world and the Innu “way of being”. We present some of the singers, groups and songs that are representative of contemporary Innu musical expression and who have had a significant impact within their society. This provides a sensitive understanding of the context, the significance and the power of these expressions.

Musique, tradition et parcours identitaire de jeunes Atikamekw. La pratique du tewehikan dans un processus de convocation culturelle - Jérôme, Laurent (Recherches amérindiennes au Québec, 2005)
À travers l’expérience d’un groupe de joueurs de tambour de la communauté atikamekw de Wemotaci, cet article montre comment de jeunes autochtones négocient le changement dans un con- texte social et culturel en pleine mutation. La pratique contemporaine du tambour est révélatrice de transformations et de persistances culturelles véhiculées par la jeunesse : valorisé dans de nombreuses communautés, le tambour s’inscrit dans un processus plus large de convocation culturelle qui a pris naissance dans la communauté de Wemotaci dans les années 80. À côté de la responsabilité culturelle que cette pratique implique, les membres du groupe revendiquent aujourd’hui une responsabilité professionnelle intervenant tout autant dans leur expérience et dans leur représentation de ce que signifie être jeune et atikamekw aujourd’hui. Les dispositions musicales, les lois du marché, le respect des contrats, les négociations et les conciliations liées à la professionnalisation se positionnent donc aux côtés des savoirs locaux persistant dans le contexte contemporain.

L'instrument de musique amérindien dans l'Est de l'Amérique du Nord : facture, usages et changements, des contacts à 1800 - Plante, Jean-François (Material Culture Review, 2005)
The problematic issue of the relations between Europeans and North American Aboriginal peoples has been widely studied during the twentieth century, but the European influence on native musical practices has not yet been explored as a general rule, nor in particular with regard to how their instruments were created and used. The voice, that manifestation of object-body-person, and its musical usage in song is without doubt the best documented musical fact in the narratives of the voyages of the civil and military officers of the New World. The historical ethnological study presented here is an initial analysis of ancient texts written between 1524 and 1800, whose purpose is to identify the changes that may have appeared in the instrumental and vocal cultures, which were closely linked to the musical art of the various Native peoples. A comparison of the collected data reveals a variety of trends in the development of native practices. In addition to these results, the work on native musical issues conducted by researchers since the end of the nineteenth century provides confirmation that in some cases acculturation and its symptoms became evident only in the nineteenth and twentieth centuries. Résumé La problématique des relations entre les Européens et les peuples autochtones d’Amérique du Nord a fait l’objet de nombreuses études au XXe siècle, mais l’influence des Européens sur les pratiques musicales amérindiennes n’a pas encore été mesurée de façon générale ni particulièrement en ce qui a trait à la fabrication et l’usage des instruments. La voix, manifestation de l’objet-corps humain, et son utilisation musicale, le chant, constituent sans doute la portion du fait musical la mieux documentée dans les récits de voyages et la corres pondance des officiers civils et militaires du Nouveau Monde. L’étude d’ethnologie historique présentée ici jette un premier regard sur des textes anciens écrits entre 1524 et 1800, afin de cerner les changements qui ont pu apparaître au sein des cultures instrumentale et vocale, très liées dans l’art musical des différents peuples autochtones. La confrontation des données recueillies permet de dégager des tendances dans l’évolution des pratiques. À ces résultats s’ajoutent les travaux sur les questions musicales amérindiennes menés par des chercheurs depuis la fin du XIX e siècle, qui viennent confirmer dans certains cas que l’inculturation et ses symptômes se sont manifestés seulement aux XIXe et XXe siècles.

Le destin des pratiques vocales autochtones entre protoethnographie, modernité et antimodernité - de Surmont, Jean-Nicolas (MUSICultures, 2004)

Chant et mission en Nouvelle-France. Espace de rencontre des cultures - Dubois, Paul-André (Université Laval, 2004)

Les Amérindiens, les missionnaires et la musique européenne - Gallat-Morin, Élizabeth; Pinson, Jean-Pierre (La vie musicale en Nouvelle-France, 2003)

Oralité et culture vocale inuit - Le Goff, Philippe (Revue DEMéter, 2003)

"Gnaah" and the Trout Song - Whidden, Lynn (Proceedings of Eighth Workshop on the Structure and Constituency of Languages of America, 2003)

Les pratiques musicales autochtones : une confluence de perspectives - Beaudry, Nicole (Traité de la culture, 2002)

Native American Contemporary Music: The Women - Diamond, Beverley (The World of Music, 2002)
This article explores issues raised in interviews with traditional and contemporary Native American musicians and recording artists of the 1990s. It exemplifies how they view their roles vis à vis traditional gender structures and community obligations, how they draw upon different media to communicate their messages, and how they use their work as a form of social action. Their narratives reveal a wide variety of strategies by which they negotiate the double consciousness and multiple relationships of their lives, balancing historically rooted values and traditions with modern ones. I attempt to develop a feminist interpretation that is respectful of the cultural values these women expressed in their conversations with me.

Des mondes religieux parallèles, un espace commun? Amérindiens et musique vocale européenne sous le Régime français - Dubois, Paul-André (Études d'histoire religieuse, 2001)
This article is devoted to the question of French religious music used by Christian Indians of New France during the 17th and 18th centuries. More particularly, it examines the surprising success of this religious and artistic practice in the post-contact North American world. It appears that cultural more than geopolitical or socioeconomic factors can explain the rapid adoption of European religious songs by Indians. In my opinion, only a better understanding of the role traditionally held by singing in the Indian culture could help us identify the cultural basis on which such a success is based. From there, it becomes possible to sustain a larger reflection about Catholicism's influence among Indians during the historical period.

Archéologie sonore. Chants amérindiens - Tremblay-Matte, Cécile; Rivard, Sylvain (Éditions Trois, 2001)
Traduit l'importance historique et culturelle des chants traditionnels des dix nations amérindiennes du Québec. Certains d'entre eux sont parvenus à passer outre l'évangélisation et l'influence de la culture européenne. Textes en langue autochtone et transcription des mélodies.